KritiK EpistEmologi tafsir KontEmporEr (studi atas Kritik Jama>l al-Banna> terhadap Beberapa pemikir al-Qur’an Kontemporer) - Saifuddin, Saifuddin; Habib, Habib (Analisis: Jurnal Studi Keislaman, 2016)
This preliminary article explains the Jamal al-Banna’s epistemological critique on Qur’anic exegesis in his book entitled Tafsir al-Qur’an Baina al-Qudama ‘wa al-muhditsin. Recent development of Qur’anic studies has witnessed some progressive  Islamic  thinkers,  those  who  have  made  such a new color on the study of the Qur’an. Starts from a brief description on the contemporary trend of Qur’anic studies, this article aims to explain Jamal al-Banna’s criticism on several Qur’anic thinkers, including Amin al-Khuli, Muh ammad Syahrur, Mohammed Arkoun, Nasr Hamid Abu Zaid, and Orientalist views on the Qur’an. It finally deals with an offer from Jamal al-Banna in the context of a new paradigm in the study of the Qur’an.